2017
DOI: 10.1111/cup.12995
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme‐like lesions in primary cutaneous aggressive cytotoxic epidermotropic CD8+ T‐cell lymphoma: A diagnostic and therapeutic challenge

Abstract: Primary cutaneous aggressive cytotoxic epidermotropic CD8+ T-cell lymphoma is an extremely rare, rapidly progressing, cutaneous lymphoma, with frequent systemic involvement and poor prognosis, that still represents a diagnostic and therapeutic challenge, especially in the early stage. Herein, we report a case of an elderly woman with a fulminant course, who at onset presented with clinical and pathological features mimicking erythema multiforme (EM) and treated with cyclosporine that led to rapid deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, this is the first a‐CGH analysis of a large cohort of pcAECyTCL patients. Only two previous molecular studies have been published: one, a single case report described by our group and included in this study; the other, a single case report concerning a 6‐year‐old child who was analyzed by means of SNP arrays that revealed numerous gains and losses suggesting genomic instability. In particular, the authors of this study found TP53 haploinsufficiency due to the loss of the entire 17p arm, and suggested that an alteration in the p14ARF/Mdm2/p53 tumor suppressor protein pathway may be associated with an unfavorable clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first a‐CGH analysis of a large cohort of pcAECyTCL patients. Only two previous molecular studies have been published: one, a single case report described by our group and included in this study; the other, a single case report concerning a 6‐year‐old child who was analyzed by means of SNP arrays that revealed numerous gains and losses suggesting genomic instability. In particular, the authors of this study found TP53 haploinsufficiency due to the loss of the entire 17p arm, and suggested that an alteration in the p14ARF/Mdm2/p53 tumor suppressor protein pathway may be associated with an unfavorable clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…1 The rarity of the entity means that its pathogenesis and molecular mechanisms are still unknown and, to the best of our knowledge, it has not yet been molecularly characterized and only two individual case reports have described genomic aberrations respectively detected by means of a single-nucleotide polymorphism array (SNP array) and arraybased comparative genomic hybridization (a-CGH). 5,6 Daniele Fanoni and Laura Corti contributed equally to this study.…”
Section: Introductionmentioning
confidence: 99%
“…The rare PCAE-TCL can be clinically misdiagnosed as more common inflammatory dermatoses such as pityriasis lichenoides et varioliformis or Mucha-Haberman disease that often has a CD8 + phenotype and possible monoclonal TCR rearrangement, 29,31 and pyoderma gangrenosum and erythema multiforme. 32 Histology and immunohistochemical studies allow a distinction between these entities.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…Recently, a study performed on tumors from 20 patients defined the copy number alteration (CNA) profile of pcAECyTCL by using array-based comparative genomic hybridization, 5 and before this, two clinical case reports included the evaluation of CNA in single patients by using array-based methods as well. 6,7 Recurrent CNA uncovered by these studies include losses within 1p, 9p, 13q and 16p as well as gains within 7q, 8q and 17q, with loss of the region containing CDKN2A/B being the most frequent CNA. 5 However, aside from the aforementioned chromosomal imbalances, causative genetic changes in pcAECyTCL remain unknown.…”
Section: Introductionmentioning
confidence: 99%